2021
DOI: 10.1016/j.idm.2021.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Assessing effects of reopening policies on COVID-19 pandemic in Texas with a data-driven transmission model

Abstract: While the Coronavirus Disease 2019 (COVID-19) pandemic continues to threaten public health and safety, every state has strategically reopened the business in the United States. It is urgent to evaluate the effect of reopening policies on the COVID-19 pandemic to help with the decision-making on the control measures and medical resource allocations. In this study, a novel SEIR model was developed to evaluate the effect of reopening policies based on the real-world reported COVID-19 data in Texas. The earlier re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…These compartmental structures reflect better the actual situation of intervention. For example, some studies have modeled intervention measures for patients with different infection status, which were common in reality: isolating asymptomatic infections at home, admitting symptomatic infections to hospital [ 40 ], and admitting severe patients to ICU for treatment [ 41 ], etc. The recovered individuals were also divided into different compartments according to whether they had been detected or not, symptomatic or asymptomatic [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…These compartmental structures reflect better the actual situation of intervention. For example, some studies have modeled intervention measures for patients with different infection status, which were common in reality: isolating asymptomatic infections at home, admitting symptomatic infections to hospital [ 40 ], and admitting severe patients to ICU for treatment [ 41 ], etc. The recovered individuals were also divided into different compartments according to whether they had been detected or not, symptomatic or asymptomatic [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…If not feasible due to public health system constraints, tracing and isolation of only household contacts is also found to significantly reduce the doubling time of the epidemic. A US-based modelling study [ 62 ] finds that increasing the capacity for detection, contact tracing and quarantine by at-least two folds would control the cases from rising during medium risk reopening (effective contact rate increased by three–five folds was considered as medium risk opening in the study).…”
Section: Resultsmentioning
confidence: 99%
“…Some attempts to elucidate the effects of different levels of economic activity on the spread of coronavirus in the context of exit strategies relied more commonly on applying different specifications of the susceptible/exposed/infective/recovered (SEIR) model. Using the SEIR model as their methodological anchor, authors estimated the COVID-19 epidemic parameters based on the data of reported infected cases and deaths in different parts of the world to predict the future epidemics of COVID-19 under different reopening policies (Chang et al 2020 ; Liu et al 2020 ; Yu et al 2021 ). This section takes an alternative route to assess the COVID-19 exit strategy designed to gradually lift interventions introduced to control the outbreak in the State of São Paulo.…”
Section: Economic Activity and The Spread Of Covid-19mentioning
confidence: 99%